2019
DOI: 10.5194/bg-16-4829-2019
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale heterogeneity of trace metals including rare earth elements and yttrium in deep-sea sediments and porewaters of the Peru Basin, southeastern equatorial Pacific

Abstract: Abstract. Due to its remoteness, the deep-sea floor remains an understudied ecosystem of our planet. The patchiness of existing data sets makes it difficult to draw conclusions about processes that apply to a wider area. In our study we show how different settings and processes determine sediment heterogeneity on small spatial scales. We sampled solid phase and porewater from the upper 10 m of an approximately 7.4×13 km2 area in the Peru Basin, in the southeastern equatorial Pacific Ocean, at 4100 m water dept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Local heterogeneity of geochemical parameters is related to small scale local variability of depositional environment parameters, such as topography, biological productivity, hydrothermal effects, dissolution of nodules, or redox zonation [97]. In some parts, the elevated metal contents in CCFZ may also be related to buried hydrothermal microchimneys [98].…”
Section: Discussionmentioning
confidence: 99%
“…Local heterogeneity of geochemical parameters is related to small scale local variability of depositional environment parameters, such as topography, biological productivity, hydrothermal effects, dissolution of nodules, or redox zonation [97]. In some parts, the elevated metal contents in CCFZ may also be related to buried hydrothermal microchimneys [98].…”
Section: Discussionmentioning
confidence: 99%
“…Inside the DEA (Figure 1), disturbance experiments were conducted to assess the environmental impact produced by a plough harrow [66,67]. The DEA is spatially heterogeneous regarding the seafloor morphology, geochemical properties, and PMN distribution, with many authors highlighting the need for further research [62][63][64]68,69]. The mapped area extends north and south of the DEA (in the N-S direction) and towards the northeast (hereafter DEA-NE).…”
Section: Study Areamentioning
confidence: 99%
“…A recent gravity core inside a black patch in DEA (Figure 1) revealed that its geochemical conditions differ significantly from the surroundings, having increased organic carbon content (0.5 wt%-0.8 wt%) [69]. The increased organic carbon content might have shifted the Mn-redox closer to the seafloor, where the diagenetically mobilized Mn is released into the bottom water and thus not supporting the PMN formation [68,69,78,79]. Photos inside the black patch confirmed the absence of surficial PMN (Figure A1).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The reason of such different behaviour among REEs is unclear. The decoupling of Y and Ce from the LREEs is suggestive of fractionation likely due to preferential scavenging of individual REEs over the others [26]. The enrichment factor (EF) is a parameter widely used to asses qualitatively the inputs intensity of elements to the sediment.…”
Section: Correlations and Ce And Eu Anomaliesmentioning
confidence: 99%